Bioreactor Engineering Research and Industrial Applications I Cell Factories - Ye, Qin.; Bao, Jie.; Zhong, Jian-Jiang.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book review series presents current trends in modern biotechnology. The aim is to cover all aspects of this interdisciplinary technology where knowledge, methods and expertise are required from chemistry, biochemistry, microbiology, genetics, chemical engineering and computer science. Volumes are organized topically and provide a comprehensive discussion of developments in the respective field over the past 3-5 years. The series also discusses new discoveries and applications. Special volumes are dedicated to selected topics which focus on new biotechnological products and new processes for their synthesis and purification. In general, special volumes are edited by well-known guest editors. The series editor and publisher will however always be pleased to receive suggestions and supplementary information. Manuscripts are accepted in English.
Cost-effective synthesis of chiral chemicals using data-mined enzymes -- Metabolic regulation of bacterial cells -- Cell factories for microbial diols -- Construction of Escherichia coli cell factories for production of bulk chemicals -- Microbial Cell Factories for Production of Long Chain Alcohols -- Yeast cell factories based on surface engineering -- Cell factories of higher fungi for useful metabolite production -- Role of Microbial Communities in Petroleum Reservoirs.
Keywords: Biotechnology; Industrial microbiology; Chemical Bioengineering; Industrial Microbiology